Reflexion sur l'amenagement des forets de production dans le basin du Congo - Fargeot, C.; Forni, E.; Nasi, Robert (2004)
Management in the production forest concessions of the Congo Basin is based on rotation principles, with the concessionary industry involved at every stage in the drafting and implementation of the felling permit granted. In this process, forest organization by area, based on management inventory and indicating timber volumes, seems the most appropriate option. Management should focus on a limited number of relatively abundant species with recognized technical properties and which markets already appreciate. Rotations should be defined essentially on the basis of economic and profitability considerations, and should ideally cover the same duration as the concession and the management scheme. Applying minimum felling diameters is a way of taking biological constraints into account to avoid compromising forest regeneration and to promote the natural dynamics of the forest.